P11.01 Same-sex behaviour and experience measured on multiple occasions in a birth cohort reveals higher lifetime prevalence than would be found in a cross-sectional study. (13th September 2015) - Dickson, NP; Magner, K; Righarts, AA; Saxton, P; van Roode, T; Connor, J
Abstract : Background: Understanding sexual – including same-sex – behaviour is critical for appropriate policies to promote sexual health. While most information on current and past same-sex behaviour (SSB) is obtained from cross-sectional studies, the validity of information from these is not known. We have explored this in a cohort study in which questions on SSB were asked on multiple occasions over a prolonged age range. Methods: In the Dunedin Multidisciplinary Health and Development Study computer-presented questions on ever (and in the past year) having a same-sex partner (SSP), male anal intercourse (for men), and a same-sex experience (SSE) ("any contact you felt was sexual"), were asked of men on four occasions between ages 21–38, and of women on three occasions between 26–38. We have compared reports of lifetime SSP and SSE at age 38, with the summation of reports on all occasions. Results: Among men, at age 38, 12.4% reported ever a SSP, 5.2% ever male anal intercourse, and 14.9% ever a SSE. Based on responses from all the assessments, the respective proportions reporting these behaviours were 16.9%, 6.5% and 21.2%, increases of 36%, 25% and 42% respectively. Among the women, at age 38, 16.8% reported ever having a SSP, and 22.7% ever a SSE. Based on responses from all assessments, the respective proportions were 20.5% and 31.4%, increases of 22% and 45% respectively. Conclusions: In this cohort SSB was more common that reported from other population-based studies. There are three plausible explanations for the marked discrepancies between the lifetime SSB reported at age 38 and derived from all reports: (1) some reports at early assessments were erroneous, (2) with age participants were less willing to report past same-sex behaviour, (3) with age earlier SSB were forgotten or reinterpreted as not being sexual. The latter seems most plausible. Disclosure of interest statement: None of the authors have conflicts of interests to disclose.